2021
DOI: 10.21037/tp-21-90
|View full text |Cite
|
Sign up to set email alerts
|

Serum IgA/C3 ratio and glomerular C3 staining predict progression of IgA nephropathy in children

Abstract: Background: This retrospective study aimed to evaluate the significance of serum immunoglobulin A/ complement 3 (IgA/C3) ratio and glomerular C3 staining at the onset of disease for predicting progression of IgA nephropathy in children. Methods: A total of 41 children with IgA nephropathy were allocated to two groups according to proteinuria (proteinuria <50 mg/kg/day group and proteinuria ≥50 mg/kg/day group) to compare their clinical data. Receiver operating characteristic (ROC) curves were used to evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…, 17 2021 C3 Poland Pediatric 148 IF; plasma, turbidmetric 11.6 67 95.8 ± 33.5 1.4 (0.02–9.6) Lang et al. , 18 2021 C3; IgA/C3 ratio China Pediatric 41 IF:C3;IgA/C3: turbidmetric 9.3 63 118.8 ± 41.2 NA Wu et al. , 38 2021 C3 China Pediatric 98 IF; plasma, turbidmetric 9.7 67 108.5 ± 37.1 2.7 (1.1–8.3) Xie et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…, 17 2021 C3 Poland Pediatric 148 IF; plasma, turbidmetric 11.6 67 95.8 ± 33.5 1.4 (0.02–9.6) Lang et al. , 18 2021 C3; IgA/C3 ratio China Pediatric 41 IF:C3;IgA/C3: turbidmetric 9.3 63 118.8 ± 41.2 NA Wu et al. , 38 2021 C3 China Pediatric 98 IF; plasma, turbidmetric 9.7 67 108.5 ± 37.1 2.7 (1.1–8.3) Xie et al.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have suggested that complement activation is associated with more severe MEST-C scores, 11 , 12 , 13 , 14 , 15 whereas others have reported no significant correlation between the 2. 16 , 17 , 18 , 19 …”
mentioning
confidence: 99%
“…These serum immunological parameters were reported to be associated with kidney histological lesions or kidney outcomes of IgAN. [44][45][46][47][48][49][50] Our study had several strengths. On the analytical aspects, the method of ELISA was used in our study, which is considered the gold standard for measuring EGF because of its better sensitivity and specificity compared with other methods (such as radioimmunoassays, radioreceptor assays, enzyme immunoassays, and ultramicroELISA assay) for detection of EGF in urine.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, several researchers have reported serum IgA as diagnostic and prognostic markers of IgAN [19,20] . Recently, studies have found that serum IgA/C3 ratio had better diagnostic and prognostic value for IgAN [8,21,22] . At the beginning of the model building, we also considered including serum IgA/C3 ratio in the nomogram model, but unfortunately it did not improve the diagnostic value of the model.…”
Section: Discussionmentioning
confidence: 99%